ANALISIS PENGARUH NILAI SUKUK, LEVERAGE, LIKUIDITAS, DAN UKURAN PERUSAHAAN TERHADAP REAKSI PASAR (Studi Kasus Pada Perusahaan Konvensional non-bank yang Menerbitkan Sukuk di Indonesia Periode 2014-2019) - Amir, Muhammad Ahkamul; Indriani, Astiwi (Diponegoro Journal of Management, 2020)
Sukuk is an investment instrument that emphasizes sharia principles. This further indicates sukuk has the potential as an alternative choice for investing. The aims of this study was to investigate factors that influence market reaction on announcement of sukuk. Independent variables that used in this study are sukuk value of sukuk, leverage, liquidity (working capital to total asset and working capital to total capital), and firm size. The population in this study is conventional company sukuk issued by sukuk in the 2014-2019 period. The final sample used in this study are 51 announcements of sukuk issuance obtained by purposive sampling method. The data of announcements event was obtained throught data Bloomberg, the KSEI website, the yahoofinance site, the ojk site, and the company website. The type of data in this study is a cross section. The analytical tool used in this study is multiple linear regression analysis testing through the application of E-views 9, taht has passed the classic assumption test (normality test, multicollinearity test, heteroskedasticity test, and autocorrelation test). The results of this study are the variable value of sukuk and firm size have a positive and significant effect on market reaction while variable WCTA (working capital to total asset) has a negative and significant effect on market reaction. Variable leverage and WCTC (Working Capital to Total Capital) have a negative and insignificant effect on market reaction.